Zambezi River Basin aquifer systems: Opportunities and challenges in using freely available data sources and groundwater flow modelling for spatial exploratory analysis - Kawawa Banda; Ezio Crestaz; Roman Seliger; Haile Mengistu; James Sauramba; Marciano Saraiva (Groundwater for Sustainable Development, 2025)

Ancient DNA: a promising tool for understanding the evolutionary history of and human pressure on the highly endangered limpet Patella ferruginea - Free Espinosa; James Haile; Stewart Finlayson; Francisco Giles-Guzman; Geraldine Finlayson; Clive Finlayson; Darren A. Fa (Conservation Genetics Resources, 2024)

Circumpolar phylogeography and demographic history of beluga whales reflect past climatic fluctuations - Mikkel Skovrind; Marie Louis; Michael V. Westbury; Cristina Garilao; Kristin Kaschner; José Alfredo Samaniego Castruita; Shyam Gopalakrishnan; Steen Wilhelm Knudsen; James S. Haile; Love Dalén; Ilya G. Meshchersky; Olga V. Shpak; et al. (Molecular Ecology, 2021)
Several Arctic marine mammal species are predicted to be negatively impacted by rapid sea ice loss associated with ongoing ocean warming. However, consequences for Arctic whales remain uncertain. To investigate how Arctic whales responded to past climatic fluctuations, we analysed 206 mitochondrial genomes from beluga whales ( Delphinapterus leucas ) sampled across their circumpolar range, and four nuclear genomes, covering both the Atlantic and the Pacific Arctic region. We found four well‐differentiated mitochondrial lineages, which were established before the onset of the last glacial expansion ~110 thousand years ago. Our findings suggested these lineages diverged in allopatry, reflecting isolation of populations during glacial periods when the Arctic sea‐shelf was covered by multiyear sea ice. Subsequent population expansion and secondary contact between the Atlantic and Pacific Oceans shaped the current geographic distribution of lineages, and may have facilitated mitochondrial introgression. Our demographic reconstructions based on both mitochondrial and nuclear genomes showed markedly lower population sizes during the Last Glacial Maximum (LGM) compared to the preceding Eemian and current Holocene interglacial periods. Habitat modelling similarly revealed less suitable habitat during the LGM (glacial) than at present (interglacial). Together, our findings suggested the association between climate, population size, and available habitat in belugas. Forecasts for year 2100 showed that beluga habitat will decrease and shift northwards as oceans continue to warm, putatively leading to population declines in some beluga populations. Finally, we identified vulnerable populations which, if extirpated as a consequence of ocean warming, will lead to a substantial decline of species‐wide haplotype diversity.

Submarine groundwater discharge drives nitrous oxide source/sink dynamics in a metropolitan estuary - Michael J. Reading; Douglas R. Tait; Damien T. Maher; Luke C. Jeffrey; Rogger E. Correa; James P. Tucker; Haile A. Shishaye; Isaac R. Santos (Limnology and Oceanography, 2021)
Coastal waterways can be significant sources of the potent greenhouse gas nitrous oxide (N 2 O) due to nitrogen inputs and eutrophication. Here, we quantify groundwater derived N 2 O inputs and atmospheric emissions within a modified urban embayment (Sydney Harbour, Australia). Overall, we found low N 2 O saturation (91–171%) and air–water fluxes (−2.2 to 24.6 μ mol m −2 d −1 ). Concentrations were highest in upstream brackish areas and a commercial/industrial subembayment. Dissolved inorganic nitrogen concentrations were low and inversely correlated to N 2 O throughout the harbor. N 2 O surface water dynamics were apparently driven by saline submarine groundwater discharge, as quantified by the radioisotope tracer radon‐222. Groundwater discharge was highest within the embayments and mangrove‐lined upper estuary. While groundwater was a net N 2 O source to surface waters, two upstream sub‐embayments featured groundwater N 2 O concentrations lower than surface water, suggesting a sink driven by surface waters recirculating in intertidal sediments. Surface‐water N 2 O was undersaturated within one upstream embayment, likely due to N 2 O consumption within sediments. Contrastingly, the downstream embayments featured higher groundwater N 2 O and accounted for 45% ± 21% of the groundwater N 2 O flux. Sydney Harbour was a net source of N 2 O to the atmosphere (mean 0.6 ± 0.3 μ mol m −2 d −1 ) with larger N 2 O fluxes occurring from relatively small areas. N 2 O emissions (expressed in CO 2 equilivents) were equivalent to 17% of CO 2 emission estimates from previous studies. The low N 2 O emissions in Sydney Harbour contrast with other modified estuaries which often emit higher N 2 O fluxes due to larger nitrogen inputs.

Novel method to quantify phenotypic markers of HIV-associated neurocognitive disorder in a murine SCID model - Christina Gavegnano; Woldeab Haile; Raj Koneru; Selwyn J. Hurwitz; James J. Kohler; William R. Tyor; Raymond F. Schinazi (Journal of NeuroVirology, 2020)

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

On the Ground or in the Air? A Methodological Experiment on Crop Residue Cover Measurement in Ethiopia - Frédéric Kosmowski; James Stevenson; Jeff Campbell; Alemayehu Ambel; Asmelash Haile Tsegay (Environmental Management, 2017)

Ancient DNA reveals complexity in the evolutionary history and taxonomy of the endangered Australian brush-tailed bettongs (Bettongia: Marsupialia: Macropodidae: Potoroinae) - Dalal Haouchar; Carlo Pacioni; James Haile; Matthew C. McDowell; Alexander Baynes; Matthew J. Phillips; Jeremy J. Austin; Lisa C. Pope; Michael Bunce (Biodiversity and Conservation, 2016)

Risk of colorectal cancer for people with a mutation in both a MUTYH and a DNA mismatch repair gene - Aung Ko Win; Jeanette C. Reece; Daniel D. Buchanan; Mark Clendenning; Joanne P. Young; Sean P. Cleary; Hyeja Kim; Michelle Cotterchio; James G. Dowty; Robert J. MacInnis; Katherine M. Tucker; Ingrid M. Winship; et al. (Familial Cancer, 2015)

Who's for dinner? High‐throughput sequencing reveals bat dietary differentiation in a biodiversity hotspot where prey taxonomy is largely undescribed - Joanna M. Burgar; Daithi C. Murray; Michael D. Craig; James Haile; Jayne Houston; Vicki Stokes; Michael Bunce (Molecular Ecology, 2014)
Effective management and conservation of biodiversity requires understanding of predator–prey relationships to ensure the continued existence of both predator and prey populations. Gathering dietary data from predatory species, such as insectivorous bats, often presents logistical challenges, further exacerbated in biodiversity hot spots because prey items are highly speciose, yet their taxonomy is largely undescribed. We used high‐throughput sequencing ( HTS ) and bioinformatic analyses to phylogenetically group DNA sequences into molecular operational taxonomic units ( MOTU s) to examine predator–prey dynamics of three sympatric insectivorous bat species in the biodiversity hotspot of south‐western Australia. We could only assign between 4% and 20% of MOTU s to known genera or species, depending on the method used, underscoring the importance of examining dietary diversity irrespective of taxonomic knowledge in areas lacking a comprehensive genetic reference database. MOTU analysis confirmed that resource partitioning occurred, with dietary divergence positively related to the ecomorphological divergence of the three bat species. We predicted that bat species' diets would converge during times of high energetic requirements, that is, the maternity season for females and the mating season for males. There was an interactive effect of season on female, but not male, bat species' diets, although small sample sizes may have limited our findings. Contrary to our predictions, females of two ecomorphologically similar species showed dietary convergence during the mating season rather than the maternity season. HTS ‐based approaches can help elucidate complex predator–prey relationships in highly speciose regions, which should facilitate the conservation of biodiversity in genetically uncharacterized areas, such as biodiversity hotspots.

Molecular‐ and pollen‐based vegetation analysis in lake sediments from central S candinavia - Laura Parducci; Irina Matetovici; Sonia L. Fontana; K. D. Bennett; Yoshihisa Suyama; James Haile; Kurt H. Kjær; Nicolaj K. Larsen; Andreas D. Drouzas; Eske Willerslev (Molecular Ecology, 2013)
Plant and animal biodiversity can be studied by obtaining DNA directly from the environment. This new approach in combination with the use of generic barcoding primers (metabarcoding) has been suggested as complementary or alternative to traditional biodiversity monitoring in ancient soil sediments. However, the extent to which metabarcoding truly reflects plant composition remains unclear, as does its power to identify species with no pollen or macrofossil evidence. Here, we compared pollen‐based and metabarcoding approaches to explore the H olocene plant composition around two lakes in central S candinavia. At one site, we also compared barcoding results with those obtained in earlier studies with species‐specific primers. The pollen analyses revealed a larger number of taxa (46), of which the majority (78%) was not identified by metabarcoding. The metabarcoding identified 14 taxa ( MTU s), but allowed identification to a lower taxonomical level. The combined analyses identified 52 taxa. The barcoding primers may favour amplification of certain taxa, as they did not detect taxa previously identified with species‐specific primers. Taphonomy and selectiveness of the primers are likely the major factors influencing these results. We conclude that metabarcoding from lake sediments provides a complementary, but not an alternative, tool to pollen analysis for investigating past flora. In the absence of other fossil evidence, metabarcoding gives a local and important signal from the vegetation, but the resulting assemblages show limited capacity to detect all taxa, regardless of their abundance around the lake. We suggest that metabarcoding is followed by pollen analysis and the use of species‐specific primers to provide the most comprehensive signal from the environment.

New environmental metabarcodes for analysing soil DNA: potential for studying past and present ecosystems - LAURA S. EPP; SANNE BOESSENKOOL; EVA P. BELLEMAIN; JAMES HAILE; ALFONSO ESPOSITO; TIAYYBA RIAZ; CHRISTER ERSÉUS; VLADIMIR I. GUSAROV; MARY E. EDWARDS; ARILD JOHNSEN; HANS K. STENØIEN; KRISTIAN HASSEL; et al. (Molecular Ecology, 2012)
Metabarcoding approaches use total and typically degraded DNA from environmental samples to analyse biotic assemblages and can potentially be carried out for any kinds of organisms in an ecosystem. These analyses rely on specific markers, here called metabarcodes, which should be optimized for taxonomic resolution, minimal bias in amplification of the target organism group and short sequence length. Using bioinformatic tools, we developed metabarcodes for several groups of organisms: fungi, bryophytes, enchytraeids, beetles and birds. The ability of these metabarcodes to amplify the target groups was systematically evaluated by (i) in silico PCRs using all standard sequences in the EMBL public database as templates, (ii) in vitro PCRs of DNA extracts from surface soil samples from a site in Varanger, northern Norway and (iii) in vitro PCRs of DNA extracts from permanently frozen sediment samples of late‐Pleistocene age (∼16 000–50 000 years bp ) from two Siberian sites, Duvanny Yar and Main River. Comparison of the results from the in silico PCR with those obtained in vitro showed that the in silico approach offered a reliable estimate of the suitability of a marker. All target groups were detected in the environmental DNA, but we found large variation in the level of detection among the groups and between modern and ancient samples. Success rates for the Pleistocene samples were highest for fungal DNA, whereas bryophyte, beetle and bird sequences could also be retrieved, but to a much lesser degree. The metabarcoding approach has considerable potential for biodiversity screening of modern samples and also as a palaeoecological tool.

Meta‐barcoding of ‘dirt’ DNA from soil reflects vertebrate biodiversity - KENNETH ANDERSEN; KAREN LISE BIRD; MORTEN RASMUSSEN; JAMES HAILE; HENRIK BREUNING‐MADSEN; KURT H. KJÆR; LUDOVIC ORLANDO; M. THOMAS P. GILBERT; ESKE WILLERSLEV (Molecular Ecology, 2012)
DNA molecules originating from animals and plants can be retrieved directly from sediments and have been used for reconstructing both contemporary and past ecosystems. However, the extent to which such ‘dirt’ DNA reflects taxonomic richness and structural diversity remains contentious. Here, we couple second generation high‐throughput sequencing with 16S mitochondrial DNA (mtDNA) meta‐barcoding, to explore the accuracy and sensitivity of ‘dirt’ DNA as an indicator of vertebrate diversity, from soil sampled at safari parks, zoological gardens and farms with known species compositions. PCR amplification was successful in the full pH range of the investigated soils (6.2 ± 0.2 to 8.3 ± 0.2), but inhibition was detected in extracts from soil of high organic content. DNA movement (leaching) through strata was evident in some sporadic cases and is influenced by soil texture and structure. We find that DNA from the soil surface reflects overall taxonomic richness and relative biomass of individual species. However, one species that was recently introduced was not detected. Furthermore, animal behaviour was shown to influence DNA deposition rates. The approach potentially provides a quick methodological alternative to classical ecological surveys of biodiversity, and most reliable results are obtained with spatial sample replicates, while relative amounts of soil processed per site is of less importance.

Islands in the ice: detecting past vegetation on Greenlandic nunataks using historical records and sedimentary ancient DNA Meta‐barcoding - TINA JØRGENSEN; KURT H. KJÆR; JAMES HAILE; MORTEN RASMUSSEN; SANNE BOESSENKOOL; KENNETH ANDERSEN; ERIC COISSAC; PIERRE TABERLET; CHRISTIAN BROCHMANN; LUDOVIC ORLANDO; M. THOMAS P. GILBERT; ESKE WILLERSLEV (Molecular Ecology, 2012)
Nunataks are isolated bedrocks protruding through ice sheets. They vary in age, but represent island environments in ‘oceans’ of ice through which organism dispersals and replacements can be studied over time. The J.A.D. Jensen’s Nunataks at the southern Greenland ice sheet are the most isolated nunataks on the northern hemisphere – some 30 km from the nearest biological source. They constitute around 2 km 2 of ice‐free land that was established in the early Holocene. We have investigated the changes in plant composition at these nunataks using both the results of surveys of the flora over the last 130 years and through reconstruction of the vegetation from the end of the Holocene Thermal Maximum (5528 ± 75 cal year BP) using meta‐barcoding of plant DNA recovered from the nunatak sediments ( sed aDNA). Our results show that several of the plant species detected with sed aDNA are described from earlier vegetation surveys on the nunataks (in 1878, 1967 and 2009). In 1967, a much higher biodiversity was detected than from any other of the studied periods. While this may be related to differences in sampling efforts for the oldest period, it is not the case when comparing the 1967 and 2009 levels where the botanical survey was exhaustive. As no animals and humans are found on the nunataks, this change in diversity over a period of just 42 years must relate to environmental changes probably being climate‐driven. This suggests that even the flora of fairly small and isolated ice‐free areas reacts quickly to a changing climate.

Blocking human contaminant DNA during PCR allows amplification of rare mammal species from sedimentary ancient DNA - SANNE BOESSENKOOL; LAURA S. EPP; JAMES HAILE; EVA BELLEMAIN; MARY EDWARDS; ERIC COISSAC; ESKE WILLERSLEV; CHRISTIAN BROCHMANN (Molecular Ecology, 2012)
Analyses of degraded DNA are typically hampered by contamination, especially when employing universal primers such as commonly used in environmental DNA studies. In addition to false‐positive results, the amplification of contaminant DNA may cause false‐negative results because of competition, or bias, during the PCR. In this study, we test the utility of human‐specific blocking primers in mammal diversity analyses of ancient permafrost samples from Siberia. Using quantitative PCR (qPCR) on human and mammoth DNA, we first optimized the design and concentration of blocking primer in the PCR. Subsequently, 454 pyrosequencing of ancient permafrost samples amplified with and without the addition of blocking primer revealed that DNA sequences from a diversity of mammalian representatives of the Beringian megafauna were retrieved only when the blocking primer was added to the PCR. Notably, we observe the first retrieval of woolly rhinoceros ( Coelodonta antiquitatis ) DNA from ancient permafrost cores. In contrast, reactions without blocking primer resulted in complete dominance by human DNA sequences. These results demonstrate that in ancient environmental analyses, the PCR can be biased towards the amplification of contaminant sequences to such an extent that retrieval of the endogenous DNA is severely restricted. The application of blocking primers is a promising tool to avoid this bias and can greatly enhance the quantity and the diversity of the endogenous DNA sequences that are amplified.

A comparative study of ancient sedimentary DNA, pollen and macrofossils from permafrost sediments of northern Siberia reveals long‐term vegetational stability - TINA JØRGENSEN; JAMES HAILE; PER MÖLLER; ANDREI ANDREEV; SANNE BOESSENKOOL; MORTEN RASMUSSEN; FRANK KIENAST; ERIC COISSAC; PIERRE TABERLET; CHRISTIAN BROCHMANN; NANCY H. BIGELOW; KENNETH ANDERSEN; et al. (Molecular Ecology, 2012)
Although ancient DNA from sediments ( sed aDNA) has been used to investigate past ecosystems, the approach has never been directly compared with the traditional methods of pollen and macrofossil analysis. We conducted a comparative survey of 18 ancient permafrost samples spanning the Late Pleistocene (46–12.5 thousand years ago), from the Taymyr Peninsula in northern Siberia. The results show that pollen, macrofossils and sed aDNA are complementary rather than overlapping and, in combination, reveal more detailed information on plant palaeocommunities than can be achieved by each individual approach. Sed aDNA and macrofossils share greater overlap in plant identifications than with pollen, suggesting that sed aDNA is local in origin. These two proxies also permit identification to lower taxonomic levels than pollen, enabling investigation into temporal changes in species composition and the determination of indicator species to describe environmental changes. Combining data from all three proxies reveals an area continually dominated by a mosaic vegetation of tundra‐steppe, pioneer and wet‐indicator plants. Such vegetational stability is unexpected, given the severe climate changes taking place in the Northern Hemisphere during this time, with changes in average annual temperatures of >22 °C. This may explain the abundance of ice‐age mammals such as horse and bison in Taymyr Peninsula during the Pleistocene and why it acted as a refugium for the last mainland woolly mammoth. Our finding reveals the benefits of combining sed aDNA, pollen and macrofossil for palaeovegetational reconstruction and adds to the increasing evidence suggesting large areas of the Northern Hemisphere remained ecologically stable during the Late Pleistocene.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.